Pharmacological and non-pharmacological treatments for major depressive disorder: review of systematic reviews. Issue 6 (14th June 2017) - Gartlehner, Gerald; Wagner, Gernot; Matyas, Nina; Titscher, Viktoria; Greimel, Judith; Lux, Linda; Gaynes, Bradley N; Viswanathan, Meera; Patel, Sheila; Lohr, Kathleen N
Abstract : Objectives: This study aims to summarise the evidence on more than 140 pharmacological and non-pharmacological treatment options for major depressive disorder (MDD) and to evaluate the confidence that patients and clinicians can have in the underlying science about their effects. Design: This is a review of systematic reviews. Data sources: This study used MEDLINE, Embase, Cochrane Library, PsycINFO and Epistemonikos from 2011 up to February 2017 for systematic reviews of randomised controlled trials in adult patients with acute-phase MDD. Methods: We dually reviewed abstracts and full-text articles, rated the risk of bias of eligible systematic reviews and graded the strength of evidence. Results: Nineteen systematic reviews provided data on 28 comparisons of interest. For general efficacy, only second-generation antidepressants were supported with high strength evidence, presenting small beneficial treatment effects (standardised mean difference: −0.35; 95% CI −0.31 to −0.38), and a statistically significantly higher rate of discontinuation because of adverse events than patients on placebo (relative risk (RR) 1.88; 95% CI 1.0 to 3.28). Only cognitive behavioural therapy is supported by reliable evidence (moderate strength of evidence) to produce responses to treatment similar to those of second-generation antidepressants (45.5% vs 44.2%; RR 1.10; 95% CI 0.93 to 1.30). All remaining comparisons of non-pharmacological treatments with second-generation antidepressants either led to inconclusive results or had substantial methodological shortcomings (low or insufficient strength of evidence). Conclusions: In contrast to pharmacological treatments, the majority of non-pharmacological interventions for treating patients with MDD are not evidence based. For patients with strong preferences against pharmacological treatments, clinicians should focus on therapies that have been compared directly with antidepressants. Trial registration number: International Prospective Register of Systematic Reviews (PROSPERO) registration number: 42016035580.